CURRENT THERAPEUTIC APPROACHES IN THE MANAGEMENT OF POLYCYSTIC OVARY SYNDROME - Wojtala, Anna; Rafałowska, Zuzanna; Rutz, Stanisław; Kret, Julia; Wyrostkiewicz , Aleksandra; Pałubska, Jagoda; Muller, Oliwer; Sadkowski, Aleksander; Bigda, Paulina; Gdula, Jan; Zielińska, Lilianna; Szpunar, Michał; et al. (International Journal of Innovative Technologies in Social Science, 2026)
Introduction. Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age and is characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. The syndrome is frequently associated with metabolic disturbances such as insulin resistance, obesity, dyslipidemia, and chronic inflammation, which increase the risk of long-term cardiometabolic complications. Due to its complex and multifactorial pathophysiology, effective management of PCOS requires a comprehensive and individualized therapeutic approach. Materials and methods. Relevant literature was identified through a structured search of PubMed and Google Scholar databases. The search included terms such as “PCOS treatment,” “PCOS pharmacological treatment,” and “PCOS alternative treatment,” followed by more specific phrases related to diet, exercise, oral contraceptives, antiandrogens, metformin, GLP-1 receptor agonists, nutritional supplements, herbal medicine, and surgical treatment. The analysis primarily included systematic reviews, meta-analyses, and randomized controlled trials in accordance with Evidence-Based Medicine (EBM) principles. Results. The reviewed evidence indicates that lifestyle modification, including weight reduction, dietary changes, and regular physical activity, remains the cornerstone of PCOS management and can significantly improve metabolic and reproductive outcomes. Pharmacological therapies such as combined oral contraceptive pills, antiandrogens, metformin, and GLP-1 receptor agonists effectively address menstrual irregularities, hyperandrogenism, and insulin resistance. In addition, nutritional supplementation and herbal medicine may provide supportive benefits by improving insulin sensitivity, reducing inflammation, and regulating hormonal balance. For patients with infertility who do not respond to pharmacological ovulation induction, laparoscopic ovarian drilling may be considered as a second-line treatment. Conclusions. PCOS management requires a multidisciplinary and individualized approach combining lifestyle interventions, pharmacological therapy, and complementary treatments. Further high-quality clinical studies are needed to better evaluate emerging therapies and optimize long-term treatment strategies for women with PCOS.